2023
DOI: 10.1111/icad.12677
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and gene flow of the soil arthropod (Scolopendra mutilans) in urban landscapes: The roles of rivers, mountains and fragmentation

Tangjun Xu,
Kexin Zhou,
Wentao Ye
et al.

Abstract: Soil invertebrates are a major element of soil biodiversity, which play critical roles in soil ecosystems. However, the impacts of urban landscapes on the genetic diversity and gene flows of soil arthropods remain unclear. Here, we studied the genetic diversity and gene flow of Scolopendra mutilans in an urban area using mitochondrial Cytb genes and eight novel microsatellite loci. A total of 22 haplotypes and 24 variation sites were identified based on 556 bp Cytb sequences from 84 individuals of five populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Many works indicate a homogenisation and decrease in functional type, species diversity and/or insect abundance as urban density increases (in this SI see: Barao et al, 2024;Casanelles-Abella et al, 2024;Federico et al, 2024;Rivest & Kharouba, 2024;Sanetra et al, 2024;Svenningsen et al, 2024). This picture is, however, nuanced (e.g., Ancillotto & Rocco, 2024;Federico et al, 2024;Ombugadu et al, 2024) and although urban areas can detrimentally impact some insect taxa through the predominance of artificial environments, constrained habitats and disturbances, other taxa can adapt and thrive in the mosaic of semi-natural and novel environments, management variation and abundant resources (Curry et al, 2024;Hill et al, 2024;Nunes et al, 2024;Plummer et al, 2024;Xu et al, 2024).…”
Section: In Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Many works indicate a homogenisation and decrease in functional type, species diversity and/or insect abundance as urban density increases (in this SI see: Barao et al, 2024;Casanelles-Abella et al, 2024;Federico et al, 2024;Rivest & Kharouba, 2024;Sanetra et al, 2024;Svenningsen et al, 2024). This picture is, however, nuanced (e.g., Ancillotto & Rocco, 2024;Federico et al, 2024;Ombugadu et al, 2024) and although urban areas can detrimentally impact some insect taxa through the predominance of artificial environments, constrained habitats and disturbances, other taxa can adapt and thrive in the mosaic of semi-natural and novel environments, management variation and abundant resources (Curry et al, 2024;Hill et al, 2024;Nunes et al, 2024;Plummer et al, 2024;Xu et al, 2024).…”
Section: In Summarymentioning
confidence: 99%
“…Peralta et al (2011) found that walls restrict movement of a leaf miner, whereas Corcos et al (2019) found that at a local scale (< 50 m), buildings acted as barriers to movement and reduced species richness of tachinid parasitoids. Conversely, the presence of ecological green corridors connecting green spaces considered as habitat patches facilitates insect movement in urban areas and enhances the metacommunities of insects, centipedes and spiders in these patches (Balbi et al, 2020; Vergnes et al, 2012; Xu et al, 2024).…”
Section: Key Emergent Themesmentioning
confidence: 99%
See 1 more Smart Citation